THE TRANSLATION OF PLACE ADJUNCTS IN THE GOLDEN R0AD BY MALE AND FEMALE TRANSLATOR - Felisia, Raden Roro Shinta (Journal of Language and Literature, 2017)
This is a translation research on how place adjuncts in an English novel are translated into Indonesian by male and female translator. The methods used in this research are descriptive and comparative method. The purposes of this study are to describe the translation of place adjuncts in The Golden Road translated into Cerita Sepanjang Musim by male translator and Hari-Hari Bahagia by female translator based on form and translation strategies, as well as to describe their similarities and differences in the translation. The result of the research shows that the translation of place adjunct by male translator mostly is in the same form and using literal translation strategy, the translation by female translator mostly is in the same form and using literal translation strategy, the similarities are occur omission strategy in every form of place adjunct, the differences are male’s translation of place adjunct using abstraction change while female’s translation does not use abstraction change and female’s translation of place adjunct use partial translation while male’s translation does not use partial translation. Keywords: Translation strategy, form, place adjunct